Oprogramowanie komputerowe wykorzystane w badaniach preferencji konsumentów metodami dekompozycyjnymi - Rybicka, Aneta (Computer Applications of Decompositional Methods Used in Marketing Research of Consumer Preferences, 2008)
In consumers preferences analysis we apply decompositional methods. This approach is being represented both by conjoint analysis and discrete choice methods. Nowadays there are many different applications that allow to conduct such research. The paper presents the characteristics of chosen computer applications that are applying conjoint methods - SPSS® 10.05 for Windows, Conjoint Analysis for Windows, CVA and CVA/HB. The SAS/STAT, CBC, CBC Advanced Design Module, CBC/HB, the Latent Class Segmentation Module and Individual Choice Estimation (ICE) Module are used in discrete choice methods research
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 27, s. 65-76